Genotype × environment interaction analysis of North American shrub willow yield trials confirms superior performance of triploid hybrids. Issue 2 (12th March 2016) - Fabio, Eric S.; Volk, Timothy A.; Miller, Raymond O.; Serapiglia, Michelle J.; Gauch, Hugh G.; Van Rees, Ken C. J.; Hangs, Ryan D.; Amichev, Beyhan Y.; Kuzovkina, Yulia A.; Labrecque, Michel; Johnson, Gregg A.; Ewy, Robert G.; et al.
Abstract: Development of dedicated bioenergy crop production systems will require accurate yield estimates, which will be important for determining many of the associated environmental and economic impacts of their production. Shrub willow ( Salix spp) is being promoted in areas of the USA and Canada due to its adaption to cool climates and wide genetic diversity available for breeding improvement. Willow breeding in North America is in an early stage, and selection of elite genotypes for commercialization will require testing across broad geographic regions to gain an understanding of how shrub willow interacts with the environment. We analyzed a dataset of first‐rotation shrub willow yields of 16 genotypes across 10 trial environments in the USA and Canada for genotype‐by‐environment interactions using the additive main effects and multiplicative interactions (AMMI) model. Mean genotype yields ranged from 5.22 to 8.58 oven‐dry Mg ha −1  yr −1 . Analysis of the main effect of genotype showed that one round of breeding improved yields by as much as 20% over check cultivars and that triploid hybrids, most notably Salix viminalis  ×  S. miyabeana, exhibited superior yields. We also found important variability in genotypic response to environments, which suggests specific adaptability could be exploited among 16 genotypes for yield gains. Strong positive correlations were found between environment main effects and AMMI parameters and growing environment temperatures. These findings demonstrate yield improvements are possible in one generation and will be important for developing cultivar recommendations and for future breeding efforts.